THE ROLE OF UNIVERSITY INCUBATORS IN STIMULATING ACADEMIC ENTREPRENEURSHIP - Stal, Eva (2016)
Many Brazilian universities have technology-based incubators, but there is a small presence of firms created by students, alumni or teachers (spin-offs). Thus, such incubators do not encourage the transfer of technologies developed in universities to society, through the creation of new businesses, one of the main ways of university-industry interaction. To test this assumption, we studied eight university incubators. As a theoretical basis, we used the concepts of open innovation and entrepreneurial university; as a methodology, we adopted a qualitative approach through the use of bibliographical, documental and field research, with in-depth interviews. Results show that there is no priority for companies created from academic research results, despite the incubators’ preference for projects that have a high potential for interaction with the university. Also, there are few efforts to attract the academic audience, which leads to underutilization of this important channel for the transfer of research results.